(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the current trends and innovative strategies in the development of mass sports in Uzbekistan. Emphasis is placed on the importance of government policies, social initiatives, and infrastructural modernization in increasing public participation in physical activities. The paper explores how integrating education, digital platforms, and community engagement models is reshaping the landscape of mass sports. It further analyzes the role of sports institutions, public-private partnerships, and international cooperation in advancing national health goals through sports development. The study provides a critical reflection on the challenges and opportunities in building a physically active society, with specific reference to the Uzbek context.